التفكير اللغوي وعلاقته بالذكاء المنظومي عند طلبة أقسام اللغة العربية في كليات التربية - م. سعد فهد داخل الدلفي (مجلة كلية التربية, 2026)
يرمي البحث الحالي الى تعرّف التفكير اللغوي وعلاقته بالذكاء المنظومي عند طلبة أقسام اللغة العربية في كليات التربية، إذ بلغ عدد افراد العينة (140) طالبًا من المجتمع الكلي من طلبة أقسام اللغة العربية في كليات التربية، للعام الدراسي(2024 / 2025)، ولتحقيق مرامي البحث تبنى الباحث أداةً لاختبار التفكير اللغوي، ومقياسًا لاختبار الذكاء المنظومي وبعد استخراج الخصائص السيكومترية طبقهما الباحث على عينه البحث، وبعد توظيف المعالجات الاحصائية الملائمة للبحث، تبين أنّ هناك فرقًا ذو دلالة احصائية في متوسط درجات اختبار التفكير اللغوي (ايجابيًا)، وهذا يدل على أنّ عينة البحث يمتلكون التفكير اللغوي، وكذلك تبين أنَّ هناك فرقًا ذو دلالة احصائية في متوسط درجات اختبار الذكاء المنظومي ( ايجابيًا)، وهذا يدل على أنَّ عينة البحث يتمتعون بالذكاء المنظومي، أما العلاقة بين التفكير اللغوي والذكاء المنظومي ، فقد اشارت النتائج الى وجود علاقة ارتباطية دالة بين التفكير اللغوي  والذكاء المنظومي، عند طلبة أقسام اللغة العربية ، وفي ضوء هذه النتائج أوصى الباحث عددًا من التوصيات والمقترحات.The present research aims to identify linguistic thinking and its relationship to systemic intelligence among students of the Arabic Language departments in Colleges of Education. The sample consisted of (140) students from the total population of students in the Arabic Language departments in Colleges of Education for the academic year (2024 / 2025). To achieve the research objectives, the researcher adopted a tool for testing linguistic thinking and a scale for testing systemic intelligence. After extracting the psychometric properties, the researcher applied them to the research sample. After employing the appropriate statistical treatments for the research, it was found that there is a statistically significant difference in the mean scores of the linguistic thinking test (positively), indicating that the research sample possesses linguistic thinking. It was also found that there is a statistically significant difference in the mean scores of the systemic intelligence test (positively), indicating that the research sample enjoys systemic intelligence. As for the relationship between linguistic thinking and systemic intelligence, the results indicated the existence of a significant correlational relationship between linguistic thinking and systemic intelligence among students of the Arabic Language departments. In light of the results, the researcher recommended a number of recommendations and suggestions
Keywords: التفكير اللغوي - الذكاء المنظومي – أقسام اللغة العربية